2021
DOI: 10.2147/jir.s312925
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Inflammation Markers Partly Explain the Link Between the Dietary Inflammatory Index and Depressive Symptoms

Abstract: Background Depression is a mood disorder characterized by a high rate of resistance to pharmacological treatments, which has often been linked to chronic inflammation. This can be influenced by different environmental factors, in particular pro-inflammatory diets. However, a mediating role of circulating inflammation has never been observed. Aim To test the association between a dietary inflammatory index (DII ® ) and continuous depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…Similarly, the weight of somatic/neurovegetative (e.g., fatigue, psychomotor retardation, and altered appetite) and cognitive/psychological symptoms of depression (e.g., low mood, anhedonia, self-estimate, and suicidality) in this link is largely neglected, as well as the role of inflammation in these specific domains. Clarifying these aspects is of utter importance in light of two main findings: first, the association of somatic symptoms with circulating inflammation markers, consistently supported by independent studies ( 24 30 ), and second, a potential explanatory role of circulating inflammation in the relationship between the inflammatory potential of diet and the severity of depressive symptoms, which was prominent for somatic but not for cognitive symptoms, as supported by recent evidence ( 31 ). Here, we further explored the influence of depression severity on mortality and hospitalization risk for all and CVD causes by (i) analyzing potential effect modifications of gender, (ii) testing the independent influence of somatic and cognitive depressive symptoms on these clinical outcomes, and iii) examining in detail the potential mediation role of the single component biomarkers of INFLA score.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Similarly, the weight of somatic/neurovegetative (e.g., fatigue, psychomotor retardation, and altered appetite) and cognitive/psychological symptoms of depression (e.g., low mood, anhedonia, self-estimate, and suicidality) in this link is largely neglected, as well as the role of inflammation in these specific domains. Clarifying these aspects is of utter importance in light of two main findings: first, the association of somatic symptoms with circulating inflammation markers, consistently supported by independent studies ( 24 30 ), and second, a potential explanatory role of circulating inflammation in the relationship between the inflammatory potential of diet and the severity of depressive symptoms, which was prominent for somatic but not for cognitive symptoms, as supported by recent evidence ( 31 ). Here, we further explored the influence of depression severity on mortality and hospitalization risk for all and CVD causes by (i) analyzing potential effect modifications of gender, (ii) testing the independent influence of somatic and cognitive depressive symptoms on these clinical outcomes, and iii) examining in detail the potential mediation role of the single component biomarkers of INFLA score.…”
Section: Introductionmentioning
confidence: 80%
“…Here, we untangled the role of specific circulating inflammatory markers in the influence of depression severity on mortality and hospitalization risk, further elucidating differential associations within gender strata and with depressive symptom domains. Figure adapted from 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, awareness has been raised regarding the relationship among obesity, depression and diet-related inflammation ( 46 , 47 ). Gialluisi et al ( 46 ) showed that the low-grade inflammation (INFLA)-score, based on four circulating inflammatory biomarkers (C-reactive protein, granulocyte-to-lymphocyte ratio, platelet and white blood cell counts), could explain the association between depressive symptoms and the dietary inflammatory index.…”
Section: Discussionmentioning
confidence: 99%